Sounding the Indian Ocean Musical Circulations in the Afro-Asiatic Seascape - Sykes, Jim (University of California Press, 2023)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. Sounding the Indian Ocean is the first volume to integrate the fields of ethnomusicology and Indian Ocean studies. Drawing on historical and ethnographic approaches, the book explores what music reveals about mobility, diaspora, colonialism, religious networks, media, and performance. Collectively, the chapters examine different ways the Indian Ocean might be "heard" outside of a reliance on colonial archives and elite textual traditions, integrating methods from music and sound studies into the history and anthropology of the region. Challenging the area studies paradigm-which has long cast Africa, the Middle East, and Asia as separate musical cultures-the book shows how music both forms and crosses boundaries in the Indian Ocean world.